Effect of tube diameter on elongated bubble length in mini channels - Venkatesan, M; Balakrishnan, A R; Das, S K (2010 3rd International Conference on Thermal Issues in Emerging Technologies Theory and Applications, 2010)
The effect of superficial velocity of liquid and gas on elongated bubble length is experimentally studied using water and air as the working fluid inside mini channels of tube diameters less than 3 mm. A high speed CMOS camera is used to identify the slug length. The reduction in tube diameter results in squeezing of bubbles and thereby results in elongated bubble flow pattern distinguishing it from slug flow pattern. At low superficial gas velocities inside mini/micro channels, such pattern dominates which is the subject of interest in the present study. The experimental set-up used in this study is designed for adiabatic co-current flow of air-water mixtures in round horizontal tubes. Both the liquid and gas streams flowed separately through a bank of rota meters and Coriolis mass flow meters before entering the gas-liquid mixer. The gas-liquid mixer installed upstream of the test section (the observation zone), ensures that the two phases get thoroughly mixed before entering the test section. Flow patterns were observed and the video graphs were recorded in a computer and subsequently analyzed frame by frame with appropriate image processing technique to determine various flow regimes. The decreasing tube diameter results in the elongated bubble flow pattern over a wider range in the flow regime map of mini channels which would be of a slug flow pattern in conventional tube diameters. The region of slug flow is differentiated from elongated bubble flow based on flow visualizations. The analysis of measured length of elongated bubble acts as a good indicator for identifying the change of flow regime in mini channels.